DC-Link Capacitor RMS Current of CHB Inverter Under Open-Switch Failures - Ko, Youngjong; Baek, Ju Yoen; Shin, Eun Kyeol; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2024)
Cascaded H-Bridge (CHB) inverters are gaining popularity in high-power applications for their flexible power scalability using low-voltage rated power semiconductor devices. However, the rise in the number of these devices and their susceptibility to failures raises concerns about reliability. Current efforts to improve reliability have mainly concentrated on detecting faults, locating them, and implementing methods to tolerate switching device failures. However, interestingly, the potential impact of failures on DC-link capacitors has been disregarded, even though capacitors are another significant cause of failures. This study aims to analyze how open-switch failures influence DC-link capacitor currents. The analysis takes into account modulation strategies of both phase-shifted carriers and level-shifted carriers. The root mean square (rms) capacitor current is derived mathematically for situations where the CHB inverter experiences an open-switch failure. The theoretical findings are subsequently validated through experimental results.
Keywords: 'current; Capacitor current; Cascaded H-bridge; Cascaded H-bridge inverte; Cascaded H-bridge inverters; Dc-link; DC-link capacitor root mean square current; Open-switch failure; Root-mean-square current; Switch failure; Cascaded H-bridge inverter; DC-link capacitor rms current; Open-switch failure